Finite element modeling, validation, and parametric investigations of a retinal reattachment stent. (24th May 2017) - Rusovici, R.; Dalli, D.; Mitra, K.; Ganiban, G.; Grace, M.; Mazzocchi, R.; Calhoun, M.
Abstract: A new retinal reattachment surgical procedure is based on a stent that is deployed to press the retina back in place. An eye‐stent finite element model studied the strain induced by the stent on retina. Finite element model simulations were performed for several stent geometric configurations (number of loops, wire diameter, and intraocular pressure). The finite element model was validated against experiment. Parametric studies demonstrated that stents could be successfully designed so that the maximum strain would be below permanent damage strain threshold of 2%. Abstract : A new retinal reattachment surgical procedure is based on a stent that is deployed to press the retina back in place. An eye‐stent finite element model studied the strain induced by the stent on retina. FEM simulations were performed for several stent geometric configurations (number of loops, wire diameter, intraocular pressure). The FEM was validated against experiment. Parametric studies demonstrated that stents could be successfully designed so that the maximum strain would be below permanent damage strain threshold of 2%.